The Genomics of Liposarcoma a Review and Commentary (Global Journal of Science Frontier Research, 2022)
Soft tissue sarcomas STS are malignancies that show mesenchymal and neuroectodermal differentiation and thus most often resemble supportive and connective tissue including fat blood vessels muscle bone tendons and nerves Over 70 subtypes of sarcomas exist and pathologists have classified these broadly according to the degree to which they resemble differentiated cell types Figure 1 1 This review will focus on the most common subset of STS in adults liposarcoma which are tumors with histological features of specialized fat cells Liposarcoma are broken down into several subtypes The four with the highest incidence are welldifferentiated liposarcoma WDLPS dedifferentiated liposarcoma DDLPS myxoid liposarcoma MLPS and pleomorphic liposarcoma PLPS 1 Overall survival is highest for MLPS followed by WDLPS and DDLPS and then PLPS2-4 Figure 2 While WDLPS occurs predominantly in the deep soft tissues of the limbs and retroperitoneum DDLPS is located mostly in the retroperitoneum MLPS and PLPS are preferentially located within the limbs5 Despite these broad categories liposarcoma can also have mixed phenotypes and is often further subdivided into even more rare entities with other ultra-rare features For instance pleomorphic MLPS has attributes of both PLPS and MLPS 6 7